Improving Football Dribbling Skill Through the Play Method at SSB Harapan Bangsa Central Bengkulu Regency Aged 10-12 Years - Oddie Barnanda Rizky; Yarmani; Tono Sugihartono; Andes Permadi; Andika Prabowo (UNIB Press, 2023)
This study aims to improve football dribbling skills in Harapan Bangsa SSB players in Central Bengkulu Regency aged 10-12 years. The research method used is an action research method designed by Kemmis and Mc Taggart. The subjects in this study were 24 SSB Harapan Bangsa players aged 10-12 years. Data collection techniques in this study used football dribbling skills test assessment instruments, field notes, and documentation. Data analysis techniques in this study used quantitative and qualitative data analysis.This study began with a football dribbling skill test of 24 players, but only 6 players (25%) had effective skills. However, these results are still far from the success criteria set for training. In Cycle I, 8 meetings were held and only 17 players (71%) had effective skills when compared to the success criteria. The research then continued into Cycle II with the addition of playing methods, but only 5 meetings were held because it showed a significant increase, namely 21 players (87.5%) had effective skills. Based on these results, the playing method proved to be effective in the process of improving football dribbling skills. The players looked happy, excited and eager to join the training.